1988
DOI: 10.1080/14640748808402284
|View full text |Cite
|
Sign up to set email alerts
|

Skill in Map Reading and Memory for Maps

Abstract: Studies of expertise have typically shown that experts have better memory for materials from their fields than do novices. However, previous research on memory for maps has not shown the expected effect of expertise. The present study differed from previous studies by using contour maps as well as planimetric maps. In Experiment 1 the expected superiority in memory performance was found for skilled map readers when contour maps were used, but not when planimetric maps were used. In Experiment 2, the main resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
49
0
2

Year Published

1990
1990
2010
2010

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(56 citation statements)
references
References 7 publications
5
49
0
2
Order By: Relevance
“…For example, Lowe [15] discussed "secondary structure", where adjacent isobars on a meteorological map together indicate a global trend of the area's barometric situation. Gilhooly et al [8] found the use of "specialist schemata" in geographers' reading of contour maps, where visual patterns formed by several contour lines indicate some global structures in the area, such as valleys and interlocking spurs. Ratwani et al [21] distinguished "specific information" and "integrating information" that can be extracted from choro- Fig.…”
Section: Problemmentioning
confidence: 99%
“…For example, Lowe [15] discussed "secondary structure", where adjacent isobars on a meteorological map together indicate a global trend of the area's barometric situation. Gilhooly et al [8] found the use of "specialist schemata" in geographers' reading of contour maps, where visual patterns formed by several contour lines indicate some global structures in the area, such as valleys and interlocking spurs. Ratwani et al [21] distinguished "specific information" and "integrating information" that can be extracted from choro- Fig.…”
Section: Problemmentioning
confidence: 99%
“…Indeed, one of the problems with most of the maps employed in studies comparing verbal with spatial processing is that they are fictitious maps whose structure and functions do not correspond to those of real geographical maps as systems of representation (Gilhooly et al, 1988;Ormrod, et al 1988;Van der Schee, 1988;Van der Schee, Dijk and Westrhenen, 1992). As pointed out above, the cognitive approach to maps, just as to other types of learning materials, has for too long ignored the particular nature of maps as external systems of representation with their own codes and epistemic functions.…”
Section: Introductionmentioning
confidence: 99%
“…What appears to distinguish effective processing of a map is a selective or strategic approach to the information in it (Thorndyke and Stasz, 1980), as well as the possession of specific knowledge about the representations specifically contained in maps (e.g., Gilhooly et al, 1988;Ormrod, et al 1988;Lowe, 1993;Postigo and Pozo, 1998). Indeed, one of the problems with most of the maps employed in studies comparing verbal with spatial processing is that they are fictitious maps whose structure and functions do not correspond to those of real geographical maps as systems of representation (Gilhooly et al, 1988;Ormrod, et al 1988;Van der Schee, 1988;Van der Schee, Dijk and Westrhenen, 1992).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Lowe [17,18] compared the performance of meteorologists and non-meteorologists in the reproduction task of meteorological maps, and found that the maps reproduced by meteorologists more accurately preserve those combinatorial features of the original maps carrying higher-level information. In the same line of interest, Kinnear and Wood [12] and Gilhooly et al [9] compared the performance of experienced readers of topographic maps and less experienced readers, and Halpern and Bower [11] compared the performance of musicians and non-musicians in the recall task on musical scores.…”
Section: Related Workmentioning
confidence: 99%
“…For example, Lowe [18] discussed "secondary structure", where adjacent isobars on a meteorological map together indicate a global trend of the area's barometric situation. Gilhooly et al [9] found the use of "specialist schemata" in geographers' reading of contour maps, where visual patterns formed by several contour lines indicate some global structures in the area, such as valleys and interlocking spurs.…”
Section: Problemmentioning
confidence: 99%